The Global Politics of Poverty in Canada: Development Programs and Democracy, 1964-1979 - Bower, Shannon Stunden (Labour / Le Travail, 2021)
The article reviews the book, "The Global Politics of Poverty in Canada: Development Programs and Democracy, 1964-1979," by Will Langford.